A new variety of Schizachyrium (Poaceae: Andropogoneae) from South America, with notes on the infraspecific taxa of Schizachyrium tenerum - Welker, Cassiano A. Dorneles; Fieker, Carolline Zatta; Peichoto, Myriam Carolina (Phytotaxa, 2019)
A new variety of Schizachyrium tenerum from South America is described and illustrated. The new taxon (S. tenerum var. muticum) differs from the other varieties of the species (S. tenerum var. tenerum and S. tenerum var. hirtiglume) mainly by the absence of awns in the sessile spikelets, which is a very unusual character in the genus. The new variety occurs in Venezuela, Bolivia, and Brazil. A taxonomic discussion and an identification key for the infraspecific taxa of S. tenerum are also presented, as well as illustrations of all varieties of the species. Additionally, Schizachyrium tenerum var. hirtiglume is reported for the first time for Colombia.